STRATEGI PERENCANAAN PENDIDIKAN BERBASIS DATA UNTUK MENINGKATKAN MUTU SEKOLAH DI ERA SOCIETY 5.0 - Nurdin, Muh. Nur Islam (As-Sulthan Journal of Education, 2025)
This study discusses the effectiveness, challenges, and technological developments in data-based education planning in the context of the digital era. The background of this study stems from the educational needs in the Society 5.0 era, which demands 21st-century competencies and the use of data to support evidence-based decision-making. The research uses a literature study approach by reviewing articles from reputable national and international journals in the 2015–2025 period. The analysis was conducted using a thematic approach that grouped the findings into three main dimensions, namely planning effectiveness, implementation challenges, and the development of Educational Data Mining (EDM) and Learning Analytics (LA). The results of the study show that data-based planning effectively improves objectivity, equity of services, and transparency in education governance. However, its implementation faces obstacles in the form of unintegrated data quality, low data literacy among educators, infrastructure limitations, and cultural and ethical issues related to privacy. Meanwhile, the development of EDM and LA opens up opportunities for planning transformation with predictive and prescriptive approaches that support personalised learning and adaptive resource management. This study emphasises the importance of integrating technological innovation, data governance policies, and human resource capacity building to strengthen the implementation of data-based educational planning in Indonesia.